2020
DOI: 10.1177/0956797620972116
|View full text |Cite
|
Sign up to set email alerts
|

Playing With Fear: A Field Study in Recreational Horror

Abstract: Haunted attractions are illustrative examples of recreational fear in which people voluntarily seek out frightening experiences in pursuit of enjoyment. We present findings from a field study at a haunted-house attraction where visitors between the ages of 12 and 57 years ( N = 110) were equipped with heart rate monitors, video-recorded at peak scare points during the attraction, and asked to report on their experience. Our results show that enjoyment has an inverted-U-shaped relationship with fear across repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 42 publications
(50 reference statements)
3
68
2
1
Order By: Relevance
“…Importantly, a complete lack of arousal in stressful situations would be unmotivating. Indeed, enjoyment of fearful situations occurs not when there is a lack of arousal, but rather an optimal amount of arousal (Clasen et al, 2019;Andersen et al, 2020). Corroborating this, PPI Stress Immunity was not correlated with thrill-seeking in this study (r = -.03, p = .587).…”
Section: Personality Traitscontrasting
confidence: 41%
See 1 more Smart Citation
“…Importantly, a complete lack of arousal in stressful situations would be unmotivating. Indeed, enjoyment of fearful situations occurs not when there is a lack of arousal, but rather an optimal amount of arousal (Clasen et al, 2019;Andersen et al, 2020). Corroborating this, PPI Stress Immunity was not correlated with thrill-seeking in this study (r = -.03, p = .587).…”
Section: Personality Traitscontrasting
confidence: 41%
“…This is surprising given that individual differences in morbid curiosity likely exist. Moreover, research on morbid curiosity and related topics has become increasingly more common (e.g., Andersen et al, 2020;Clasen, 2012;Clasen, 2017;Clasen et al, 2019;Harrison & Frederick, 2020;Kerr, 2015;Kerr et al, 2019;Martin, 2019;Niehoff & Oosterwijk, 2020;Oosterwijk, 2017;Oosterwijk et al, 2020;Robinson et al, 2014;Scrivner 202;Scrivner & Christensen, 2021;Scrivner et al, 2020;Stone & Sharpley, 2008;Vicary & Fraley, 2010;Wabnegger et al, 2021). This boom in research -largely in the field of psychology -on morbid curiosity and related psychological and behavioral phenomena implies that the construct is interesting, relevant, and in need of theoretical clarification and an appropriate assessment tool.…”
Section: Morbid Curiositymentioning
confidence: 99%
“…In support of this idea, one study found that horror fans appeared to have greater psychological resilience during the early months of the COVID-19 pandemic than non-horror fans (Scrivner et al, 2021). Thus, engaging with horror can be understood as a form of scary play that serves an important function of threat simulation (Andersen et al, 2020;Clasen, 2017;Kerr et al, 2019;Marks & Nesse, 1994).…”
Section: Play and The Threat Simulation Account Of Horrormentioning
confidence: 99%
“…While previous studies have documented some of the reasons why certain horror fans get enjoyment from frightening entertainment (e.g., Andersen et al, 2020;Andrade & Cohen, 2007;Tamborini & Weaver, 1996), the benefits from horror in terms of learning something about oneself and attaining personal growth are still underspecified. It is possible that White Knucklers and Dark Copers differ in terms of what they learn about themselves and what they gain in personal growth.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation